Transformational Leadership, Organizational Culture, Work Motivation on Employee Performance in Kapanewon Pengasih, Kulon Progo, Yogyakarta - Kusmaryati Dwi; Karisa Salsabila (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2023)
This study tries to ascertain how the Organizational Culture, Employee Motivation, and Leadership style of Kapanewon Pengasih Kulonprogo personnel affect their Performance. A Likert scale of five questionnaires collected samples from 100 individuals. The data were examined using Multiple Linear Regression. The study's findings demonstrate that Transformational Leadership, Organizational Culture, and Motivation significantly improve worker Performance.